Obstacles Facing Researchers and Reflections on Scientific Research in the Media Departments of Universities in the Region Kurdistan - Rozhan Muhammad Rashid; Fuad Ali Ahmed (Zanco Journal of Humanity Sciences)
The topic of this research is (obstacles facing researchers and their reflection in scientific research of the Department of Media of Kurdistan Regional Universities). r reflected in the research of the fourth year of the bachelor's degree in the evening media and The aim of the research is to determine the amount of various obstacles facing the researcher Fourth Bachelor's Degree in Morning and Evening Media, Sulaimani University and Salahaddin University This research has several implications for media and academic studies, the most important of which is (touch on another wound of the body of the Kurdish Media Academy to find a solution, in other words, identifying problems and Scientific suggestions to solve the problem)The research community includes researchers from the morning and evening media departments of the Kurdistan Regional University for the academic year (2022-2023). It is the mirror of the research, the most important conclusion that the researcher's understanding is that economic, academic and time constraints are fully reflected in the research